FACTORS RELATED TO THE IMPLEMENTATION OF NURSE HANDOVER IN THE INTERNAL MEDICINE WARD AT RSUD (REGIONAL PUBLIC HOSPITAL) PROF. DR. MARGONO SOEKARJO, PURWOKERTO - Hendri Susanto; Meida Laely Ramdani; Endiyono; Yektiningtyastuti (Nursing Sciences Journal, 2025)
The nurse handover is a technique for conveying and receiving information about patients in the most effective manner possible, involving brief, clear, and comprehensive explanations of independent nursing actions, collaborative actions that have been or need to be undertaken, and patient progress. Several factors influence the implementation of nurse handovers, including age, education level, work experience, knowledge, responsibility, communication, documentation, leadership of the head nurse, peer support, resources, nurse motivation, nurse attitudes, and coworker relationships. Objective: To identify factors related to the implementation of nurse handover. This study used a descriptive correlational quantitative method with a cross-sectional approach, employing the chi-square test. Data collection was conducted using total sampling with a questionnaire instrument distributed to 57 respondents. Results: The Chi-Square test with a significance level of 0.05 showed the following p-values for each factor: age (p = 0.005), education level (p = 0.008), work experience (p = 0.004), knowledge (p = 0.001), responsibility (p = 0.001), documentation (p = 0.000), and communication (p = 0.002). These results indicate significant correlation between age, education level, work experience, knowledge, responsibility, communication, and documentation, and the implementation of nurse handovers. Conclusion: Age, education level, work experience, knowledge, responsibility, communication, and documentation are significantly related to the implementation of nurse handovers.